EVALUASI PENGUNGKAPAN LAPORAN BERKELANJUTAN (SR) PADA PERUSAHAAN LQ45 PERIODE 2006-2011 - Ririn Breliastiti (Universitas Bunda Mulia, 2017)
Company as an economic entity has many goals such as earn high income and increase the share holder value and business’s sustainability. A company who realize the important of sustainability development will report its performance in sustainability reporting. The research’s objectives are to identify which company has report their CSR program in the annual report, report CRS in sustainability reporting, according to GRI Guidelines and also the application level of the GRI for SR making. Between 2006 and 2011, LQ45 companies which have reported their CSR program were Energi Mega Persada Tbk, Indocement Tunggal Prakarsa Tbk, Indo Tambangraya Megah Tbk, Semen Gresik (Persero) Tbk, Kawasan Industri Jababeka Tbk and Lippo Karawaci Tbk. Aneka Tambang (Persero) Tbk, International Nickel Ind Tbk, Medco Energi International Tbk, Perusahaan Gas Negara (Persero) Tbk, Semen Cibinong Tbk, Tambang Batubara Bukit Asam Tbk, Timah Tbk, United Tractors Tbk and Bakrieland Development Tbk have SR making. SR composition using GRI Guidelines have been conduct by 9 corporates as sample of the research by using GRI standard from GRI to G3 up to GRI-G3.1 aplication. Aplication level in making SR showed various result in 9 corporates, which are A+, A and B. Key Words : Sustainability Report